PAD-mediated citrullination is a novel candidate diagnostic marker and druggable target for HPV-associated cervical cancer - Albano, Camilla; Biolatti, Matteo; Mazibrada, Jasenka; Pasquero, Selina; Gugliesi, Francesca; Lo Cigno, Irene; Calati, Federica; Bajetto, Greta; Riva, Giuseppe; Griffante, Gloria; Landolfo, Santo; Gariglio, Marisa; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Citrullination is an emerging post-translational modification catalyzed by peptidyl-arginine deiminases (PADs) that convert peptidyl-arginine into peptidyl-citrulline. In humans, the PAD family consists of five isozymes (PADs 1-4, 6) involved in multiple diseases, including cancer. Given that high-risk (hr) human papillomaviruses (HPVs) are the etiological agents of cervical cancer, in this study, we sought to determine whether PAD-mediated protein citrullination would play a functional role in the HPV-driven transformation of epithelial cells. Here we show that both total protein citrullination and PAD4 expression levels are significantly associated with cervical cancer progression. Specifically, epithelial immunostaining for PAD4 revealed an increasingly higher histoscore from low-grade (CIN1) to high-grade (CIN2, CIN3) cervical intraepithelial neoplasia, and invasive squamous cell carcinoma (SCC) lesions, raising the attractive possibility that PAD4 may be used as tumor staging markers. Furthermore, taking advantage of the epidermoid cervical cancer cell line CaSki, which harbors multiple copies of the integrated HPV16 genome, we show that the expression of E6 and E7 HPV oncoproteins is impaired by treatment with the pharmacological pan-PAD inhibitor BB-Cl-amidine. Consistently, p53 and p21, two targets of HPV oncoproteins, are upregulated by the PAD inhibitor, which undergoes cell growth arrest and apoptosis. Altogether, these findings highlight a novel mechanism by which hrHPVs alter host regulatory pathways involved in cell cycle and survival to gain viral fitness, raising the possibility that PADs may represent an attractive target for developing novel host-targeting antivirals effective in preventing cervical cancer progression.